ANALISIS LAPORAN ARUS KAS UNTUK MENILAI KINERJA KEUANGAN PADA PT. TELKOM, TBK DIVRE VII KTI MAKASSAR - Mariati M Mariati M (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2014)
This study aims to determine the financial performance. Telkom, Tbk DIVRE KTI VII Makassar, to see the development of a cash flow statement using financial analysis, namely Horizontal and Vertical Knowing the extent of the usefulness of cash flows in order to assess the financial performance of companies with the method used adalahMetode descriptive analysis. This method is a presentation of data derived from the Statement of Cash Flows is prepared by the Financial Accounting Standards using the method directly. Performance Corporate Finance and will be assessed with the use of financial ratio analysis based on the cash flow statement using quantitative descriptive analysis method of comparative analysis techniques Horizontal and Vertical. Horizontal analysis of the results of the discussion of the statement of cash flows in 2010-2012 shows that the company has increased by Rp.30.553 billion in operating activities in the year 2010 to 2011, it was caused by a significant increase in cash receipts, while for the period 2110-2012 are also investing activities decreased by Rp.3.194 billion, or 22.01% . Vertical analysis for increases and decreases in net current cash and cash equivalents entry operat activity . in 2010 amounted to Rp.1.421 billion, and in 2011 this amounted to Rp.509 miliarditahun decline, whereas in 2012 again increased significantly by Rp.3.316 billion. Through the assessment of financial performance to Sales PT. Telekomunikasi Indonesia Cash Flow (Persero). Inc., in 2011, an increase of 42.48% from the previous year, while in the year 2012 decreased by 35.05%. The higher the ratio means greater returns from the sale of every dollar earned in the form of cash as well as more efficient operations or sale of the company